Clinical Applicability of Lung Ultrasound Methods in the Emergency Department to Detect Pulmonary Congestion on Computed Tomography - Miger, Kristina Cecilia; Fabricius-Bjerre, Andreas; Maschmann, Christian Peter; Wamberg, Jesper; Winkler Wille, Mathilde Marie; Abild-Nielsen, Annemette Geilager; Pedersen, Lars; Lawaetz Schultz, Hans Henrik; Damm Nybing, Janus; Nielsen, Olav Wendelboe (Ultraschall in der Medizin - European Journal of Ultrasound, 2019)
Background B-lines on lung ultrasound are seen in decompensated heart failure, but their diagnostic value in consecutive patients in the acute setting is not clear. Chest CT is the superior method to evaluate interstitial lung disease, but no studies have compared lung ultrasound directly to congestion on chest CT.Purpose To examine whether congestion on lung ultrasound equals congestion on a low-dose chest CT as the gold standard.Materials and Methods In a single-center, prospective observational study we included consecutive patients ≥ 50 years of age in the emergency department. Patients were concurrently examined by lung ultrasound and chest CT. Congestion on lung ultrasound was examined in three ways: I) the total number of B-lines, II) ≥ 3 B-lines bilaterally, III) ≥ 3 B-lines bilaterally and/or bilateral pleural effusion. Congestion on CT was assessed by two specialists blinded to all other data.Results We included 117 patients, 27 % of whom had a history of heart failure and 52 % chronic obstructive pulmonary disease. Lung ultrasound and CT were performed within a median time of 79.0 minutes. Congestion on CT was detected in 32 patients (27 %). Method I had an optimal cut-point of 7 B-lines with a sensitivity of 72 % and a specificity of 81 % for congestion. Method II had 44 % sensitivity, and 94 % specificity. Method III had a sensitivity of 88 % and a specificity of 85 %.Conclusion Pulmonary congestion in consecutive dyspneic patients ≥ 50 years of age is better diagnosed if lung ultrasound evaluates both B-lines and pleural effusion instead of B-lines alone.
Keywords: lung ultrasound; computed tomography; dyspnea; emergency department; pulmonary congestion